Active targeted HIV testing and linkage to care among men who have sex with men attending a gay sauna in Thailand. Issue 3 (4th March 2017) - Khawcharoenporn, Thana; Apisarnthanarak, Anucha; Phanuphak, Nittaya
ABSTRACT: Existing data on the feasibility of human immunodeficiency virus (HIV) testing and counseling (HTC) and linkage to care among men who have sex with men (MSM) in hotspots are currently limited. A prospective study on active targeted HTC and linkage to care among MSM (≥18 years old) was conducted at a gay sauna in Thailand from November 2013 to October 2015. HIV risks and risk perception were evaluated through an anonymous survey. HIV testing with result notification and care appointment arrangement were provided on-site. Of the 358 participants; median age was 30 years; 206/358(58%) were at high risk for HIV acquisition; 148/358(41%) accepted HTC, all of whom either had prior negative HIV tests [98/148 (66%)] or had not known their HIV status [50/148 (34%)]. The three most common reasons for declining HTC were prior HIV testing within 6 months (48%), not ready (19%) and perceiving self as no risk (11%). Of the 262 moderate- and high-risk participants, 172 (66%) had false perception of low HIV risk which was significantly associated with declining HTC. Among the 148 participants undergoing HTC, 25 (17%) were HIV-infected. Having false perception of low risk ( P  = 0.004) and age <30 years ( P  = 0.02) were independently associated with HIV positivity. Only 14 of the 25 HIV-infected participants (56%) could be contacted after the result notification, of whom 12 (86%) had established HIV care and received immediate antiretroviral therapy. The active targeted HTC and facilitating care establishment was feasible among MSM attending the gay sauna but required strategies to improve accuracy of HIV-risk perception and linkage to care.